Remaja Berdaya: Edukasi untuk Memahami dan Menghindari Kenakalan Remaja pada Siswa SMP Negeri 1 Dempar - Febrianur, Hana Giska; Maharani, Putri; Meysi, Amelia; Payuk, Seprianto; Al Dzaky, Audric; Ramlin; Kurniawan, Ridho Setya; Samsul, Erwin (ANDIL Mulawarman Journal of Community Engagement, 2024)
Juvenile delinquency has become a serious problem that requires special attention and handling, including in the environment of SMP Negeri 1 Dempar. Thus, education is determined as an effort to provide students with a deep understanding of various aspects of juvenile delinquency, its impact on themselves and the environment, and effective strategies to avoid delinquent behavior. This education is carried out using the lecture method and reaction evaluation and cognitive evaluation are carried out. The results of this activity indicate significant success in increasing understanding of adolescence, avoiding juvenile delinquency, and encouraging the development of positive life skills. This is evidenced by the results of the Wilcoxon Signed Rank Test which produces a value of p = 0.000 (p <0.05), meaning that there is a difference in student knowledge between before and after being given intervention in the form of juvenile delinquency education. KEYWORDS: Education, Juvenile Delinquency, Adolescent, Dempar